Exploring the Nexus between G20 Agendas, Green Economy Policies, and Global Financial Governance - Nugroho Putri, Adinda Ayu Melati; Rafli Alfaizi Hakim; Michelle Pinkhan Najoan; Jessica Elvira Sinurat; Wiwiek Rukmi Dwi Astuti (Universitas Sulawesi Barat, 2025)
Abstract: Global warming conditions with global dynamics that revolve around politics and economics today have created new economic conditions, namely the Green Economy. The G20 as an association of countries with the largest GDP in the world can certainly be an actor engaged in the initiation of the Green Economy in Global Governance. This article takes the theory of neoliberal institutionalism with a qualitative methodology through document studies to analyze the influence of the G20 on Green Economy policies in Global Governance. Through this analysis, the author finds out that the G20's role in Green Economy policy is still constrained by authority and bureaucracy, seeing that G20 countries in 2021 only provide little assistance for environmental recovery. This can be caused by the absence of an international regime produced by the G20. Each G20 country only ratified the Paris Agreement produced by the United Nations Framework Convention on Climate Change (UNFCCC). The lack of a resulting regime is due to the fact that the G20 is a venue for discussion and collaboration, not a governing entity with the authority to impose norms or policies. Keywords: G20, Global Governance, Green Economy Abstrak: Kondisi pemanasan global dengan dinamika global yang berputar pada politik dan ekonomi pada masa ini telah menciptakan kondisi ekonomi baru, yaitu Ekonomi Hijau. G20 sebagai perkumpulan negara dengan GDP terbesar di dunia tentunya dapat menjadi aktor yang bergerak dalam inisiasi Ekonomi Hijau dalam Tata Kelola Global. Artikel ini mengambil teori Neoliberal-Institusionalisme dengan metodologi kualitatif melalui studi dokumen untuk menganalisis pengaruh G20 dalam kebijakan Ekonomi Hijau di Tata Kelola Global. Melalui analisis ini, penulis mengetahui bahwa peran G20 dalam kebijakan Ekonomi Hijau masih terkendala oleh otoritas dan birokrasi, melihat negara-negara G20 pada 2021 hanya memberi sedikit bantuan untuk pemulihan lingkungan. Hal ini dapat disebabkan oleh ketiadaan rezim internasional yang dihasilkan oleh G20. Masing-masing negara G20 hanya meratifikasi Paris Agreement yang dihasilkan oleh United Nations Framework Convention on Climate Change (UNFCCC). Kurangnya rezim yang dihasilkan disebabkan oleh fakta bahwa G20 adalah tempat untuk berdiskusi dan berkolaborasi, bukan entitas pemerintahan yang memiliki wewenang untuk memaksakan norma atau kebijakan. Kata Kunci: Ekonomi Hijau, G20, Tata Kelola Global